Virtual Reality in Systematic Life - G V S Narayana, Mr; SubbaRao Gogulamudi, Mr; M Kavitha, Mrs; D Usha Rani, Mrs; Arun Kumar, P (International Journal of Engineering and Technology, 2018)
Past 20 years there has been a rapid growth in virtualization. With the help of Internet of Things [IOT] we can achieve so many things in Virtual Reality [VR]. IOT is the source of connecting devices together by using an address called as IP (Internet Protocol). This will help us operate devices remotely. To simply put VR is the future world. In this paper we would like to show some improvements that can be made to the present VR devices and how can it change the standards of living of people and helps us grow in all the possible ways.Â Â